DEVELOPMENT OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN THE ERA OF SOCIETY 5.0 - Fahri, Adnan Faishol; Azani, Mohammad Zakki (Tadrib: Jurnal Pendidikan Agama Islam, 2023)
The purpose of the research is to be able to provide knowledge for the problem of the Development of Islamic Religious Teachers. The development of Islamic Religious Education Teachers in the Era of Society 5.0 "This research aims to find out the development of Islamic Religious Education teachers in the era of society 5.0 Then to find out what application processes will be carried out by Islamic Religious Education teachers in the 5.0 era. In this research, researchers used qualitative research methods. This research is qualitative because it is conducted to understand the meaning behind a phenomenon that occurs by describing it in the form of words. The main technique in collecting data is a literature study, researchers will search for data in accordance with the discussion regarding the development of Islamic religious education teachers in the era of Society 5.0. The era of society 5.0 is a revolution from the industrial era 4.0 that we have faced today. In the era of society, 5.0 has a different concept from the industrial era 4.0. If the industrial era 4.0 makes AI and artificial intelligence its main components, while society 5.0 uses AI and modern technology, it just makes humans the main component. And if the era of Society 5.0 is applied in the world of education, then teaching staff or teachers here are the main components. Therefore, professional and qualified teachers are needed in order to produce a quality education world in line with the era of Society 5.0. The development of PAI teachers in facing the era of society 5.0 must also be more significant because the result or measure of the success of PAI teachers is the formation of "Insān Kāmil" (Plenary Human).